Common opportunistic infections and their CD4 cell correlates among HIV-infected patients attending at antiretroviral therapy clinic of Gondar University Hospital, Northwest Ethiopia - Damtie, Debasu (BioMed Central, 2013)
BACKGROUND: Human immunodeficiency virus (HIV) pandemic is among the greatest health crises ever faced by humanity. Morbidity and mortality in HIV disease is due to immunosuppression leading to life-threatening opportunistic infections (OIs) during the natural course of the disease. This study was aimed to assess the prevalence and CD4 correlates of OIs among adult HIV-infected patients attending at Gondar University Hospital. METHODS: Cross sectional study was conducted on 360 adult HIV-infected patients attending antiretroviral therapy clinic from February 2012-April 2012. Patients’ OI status was determined through clinical diagnosis and laboratory investigations. CD4 count was determined using flow cytometry technique. Sociodemographic and clinical data were obtained from interview and patients’ medical records. Bivariate and multivariate logistic regression analysis was done using SPSS version 16 statistical soft ware and odds ratio was used as the measure of association. P-value less than 0.05 was considered statistically significant for all tests. RESULTS: In this study, 360 HIV-infected patients were included; of whom (n = 216/360, 60%) were females. The majority of patients (n = 153/360, 42.5%) were 25-34 years old with mean age of 35.5+ 8.8 standard deviation. The overall prevalence of OIs was (n = 71/360, 19.7%). Tuberculosis (n = 35/360, 9.72%) followed by oral candidiasis (n = 18/360, 5%) and diarrhea (n = 12/360, 3.3%) were the most frequently observed OIs. CD4 count less than 200/mm(3) (OR = 4.933, P < 0.001), World Health Organization (WHO) clinical stage III (OR = 9.418, P < 0.001) and IV (OR = 22.665, P < 0.001) were found to have strong association with acquisition of OIs. CONCLUSIONS: Tuberculosis, oral candidiasis and diarrhea were the leading OIs encountered by HIV-infected patients. CD4 count less than 200/mm(3) and advanced WHO clinical stages of the disease were found to be predictors of OIs. Interventions aimed at preventing and treating HIV associated OIs are crucial. Initiation of ART before the CD4 count drops below 350 should be encouraged.